2021
DOI: 10.2147/ceg.s289269
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pancreatic Cancer in Saudi Arabia: A Retrospective Analysis of Pancreatic Cancer Diagnosed in Saudi Arabia Between 2004 and 2015

Abstract: Purpose Over the last decades, the incidence of pancreatic cancer has increased, particularly in countries with a higher socioeconomic status. The present work aimed to provide detailed epidemiological data on the incidence of pancreatic cancer in Saudi Arabia. Patients and Methods In this retrospective descriptive study, the epidemiological data on pancreatic cancer cases diagnosed in 13 administrative regions of Saudi Arabia between January 2004 and December 2015 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…This is mainly because in countries with a high HDI, life longevity increases one’s risk of developing pancreatic cancer. Also, the availability and ease of access to medical care with an advanced and systematic cancer registration may explain the increased reported incidence in such countries [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly because in countries with a high HDI, life longevity increases one’s risk of developing pancreatic cancer. Also, the availability and ease of access to medical care with an advanced and systematic cancer registration may explain the increased reported incidence in such countries [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding could be attributed to the poor prognosis that is usually associated with this type of cancer at the time of diagnosis. 18 Nevertheless, this study has reported pancreatic cancer in one patient only, thus further evaluation of such finding is needed.…”
Section: Discussionmentioning
confidence: 80%
“…Pancreatic cancer is the seventh leading cause of death worldwide, and in 2018, the International Agency for Research on Cancer estimated that the age-standardized incidence rate for pancreatic cancer in Saudi Arabia among both sexes across age groups was 2.2 per 100 000 individuals 8 . There are multiple risk factors for pancreatic cancer, one of which is obesity, as observed in our patient 9 .…”
Section: Discussionmentioning
confidence: 99%